Answer:
![\textsf{13.} \quad(x-1)^2+(y+2)^2=9](https://img.qammunity.org/2023/formulas/mathematics/college/ev96fn402xxyyb9cwkunov8pqati1ut0n8.png)
center = (1, -2)
radius = 3
![\textsf{14.} \quad y=5 \cdot 3^x](https://img.qammunity.org/2023/formulas/mathematics/college/ba8c43op9w20l9yvuuq18p28b20230jyae.png)
![\textsf{15.} \quad x=(104)/(3), \quad x=-(88)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/ui4h97yo1zft00dcjfmnquzd0pqmqotarx.png)
Explanation:
Question 13
Equation of a circle
![(x-a)^2+(y-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ilekd9w5v3ytefhk3unvr8rhka2u3mptc6.png)
(where (a, b) is the center and r is the radius)
Given equation:
![x^2+y^2-2x+4y-4=0](https://img.qammunity.org/2023/formulas/mathematics/college/n15m98okmvsd6y1uhirc2p6ao4vp5d4p2v.png)
To rewrite the given equation in graphing form, first add 4 to both sides of the equation and rearrange the variables:
![\implies x^2-2x+y^2+4y=4](https://img.qammunity.org/2023/formulas/mathematics/college/tpytfesbe9er72x6sgx1qjvmcj3gb5hefj.png)
Add the square of half the coefficients of the x and y terms to both sides:
![\implies x^2-2x+\left((-2)/(2)\right)^2+y^2+4y+\left((4)/(2)\right)^2=4+\left((-2)/(2)\right)^2+\left((4)/(2)\right)^2](https://img.qammunity.org/2023/formulas/mathematics/college/iigae8z369a2juwalue17s7w7zvq3h25wa.png)
![\implies x^2-2x+1+y^2+4y+4=9](https://img.qammunity.org/2023/formulas/mathematics/college/ux11ku2x1xuhjnt9x1ewn9k9127l2h3mmv.png)
Finally, factor both trinomials:
![\implies (x-1)^2+(y+2)^2=9](https://img.qammunity.org/2023/formulas/mathematics/college/4b21abm5nnebdi3r5coi1deumvwo5bqezt.png)
Now compare the equation in graphing form to the general equation of a circle to find the center and radius:
⇒ a = 1 and b = -2 ⇒ center = (1, -2)
⇒ r² = 9 ⇒ radius = √9 = 3
Question 14
General form of an exponential function:
![y=ab^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/hye5rg1h8wj3ohgdt4j1vpepdhoym0w9ex.png)
(where a and b are constants to be found)
Given points on the curve:
Substitute the given points into the general form of the equation to create two equations:
![\textsf{Equation 1}: \quad ab^4=405](https://img.qammunity.org/2023/formulas/mathematics/college/mhictykq382rokhe2ez04ohrn1r484ea2n.png)
![\textsf{Equation 2}: \quad ab^9=98415](https://img.qammunity.org/2023/formulas/mathematics/college/ghhg978c56vvoj13rs9naupmdo93k2ham6.png)
Divide Equation 2 by Equation 1 to eliminate a, then solve for b:
![\implies (ab^9)/(ab^4)=(98415)/(405)](https://img.qammunity.org/2023/formulas/mathematics/college/b4v7otdiak4pv73k1p52sssldj003ag3rp.png)
![\implies (b^9)/(b^4)=243](https://img.qammunity.org/2023/formulas/mathematics/college/7nmwbsor8f9btoq8ljd0sy21hjghv9mm5g.png)
![\implies b^(9-4)=243](https://img.qammunity.org/2023/formulas/mathematics/college/dcfqlo6rc1eh85ef192mh2zxwkav3yqi90.png)
![\implies b^5=243](https://img.qammunity.org/2023/formulas/mathematics/college/5uhqqc1oqme2jvd08arb91a6hjkccon6tf.png)
![\implies b=\sqrt[5]{243}](https://img.qammunity.org/2023/formulas/mathematics/college/ihj0mk21r0625avbrpcw1oszu5gx5wshtk.png)
![\implies b=3](https://img.qammunity.org/2023/formulas/mathematics/college/t45u6txnk54mnv98703jwa4ar79sdt9ti1.png)
Substitute the found value of b into one of the equations and solve for a:
![\implies a(3)^4=405](https://img.qammunity.org/2023/formulas/mathematics/college/1m9gzrfb61zwoy072z1qpf9emirzi70niu.png)
![\implies 81a=405](https://img.qammunity.org/2023/formulas/mathematics/college/xn0rfu9ld5j9xd48rxhsyk347d7rg79cfb.png)
![\implies a=(405)/(81)](https://img.qammunity.org/2023/formulas/mathematics/college/hhlxdu0y1g2yy80oi99nc2r2ls5agv9qmd.png)
![\implies a=5](https://img.qammunity.org/2023/formulas/mathematics/college/jse9io7mjdyo0i0syyx14mdwp1gm6z8g0k.png)
Therefore, the exponential equation that passes through (4, 405) and (9, 98415) is:
![y=5 \cdot 3^x](https://img.qammunity.org/2023/formulas/mathematics/college/beu0o46mx96nfaum4nqfcunggefyfpm1jo.png)
Question 15
Given equation:
![\left|(3)/(2)x-4\right|+2=50](https://img.qammunity.org/2023/formulas/mathematics/college/6ig2jmdsyv6utkk888k37hoc8kr04wqk8w.png)
Isolate the absolute value by subtracting 2 from both sides:
![\implies \left|(3)/(2)x-4\right|=48](https://img.qammunity.org/2023/formulas/mathematics/college/xzbvd8gqugpjyuybb3gy065hd0mraj3qh4.png)
Set the contents of the absolute value to positive and negative and solve for x:
Positive absolute value:
![\implies (3)/(2)x-4=48](https://img.qammunity.org/2023/formulas/mathematics/college/w6i1xd90tmgxwp4u35e320xcevogx50kio.png)
![\implies (3)/(2)x=52](https://img.qammunity.org/2023/formulas/mathematics/college/zk90dzqvb0v2afaqu58pfsrlijvtav10m6.png)
![\implies x=52 \cdot (2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/m3oy6fx2qt2355wbew6ld0fgzheh17qyts.png)
![\implies x=(104)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/w92dqv89b594gjt9saza587f95ra021n3g.png)
Negative absolute value:
![\implies -\left((3)/(2)x-4\right)=48](https://img.qammunity.org/2023/formulas/mathematics/college/jt9o20z42x1h3a06m1h8hsbm0vrbs7lx1y.png)
![\implies -(3)/(2)x+4=48](https://img.qammunity.org/2023/formulas/mathematics/college/1uxpomlhluazvziubargxx9s0n046k2wt6.png)
![\implies -(3)/(2)x=44](https://img.qammunity.org/2023/formulas/mathematics/college/g2wip5v52fac19mlv3952dhsygsycubo0l.png)
![\implies x=44 \cdot -(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/xnvp1sb3fdrkgrm48hsjoctkwcwzeztey4.png)
![\implies x=-(88)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/blu5kllukcwqsnmeaonscz7kwjx1n0v5xp.png)
Therefore, the solution to the equation is:
![x=(104)/(3), \quad x=-(88)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/ocqwd8h18x3q7d3oslekm4npx38sj1bgjk.png)